Lazismu Cileungsi's Marketing Communication in Disseminating Zakat, Infaq, And Shadaqah - Fadh Fawaz; Agus Hariyanto; Siti Saroh (Journal Research of Social Science, Economics, and Management, 2026)
By adopting Philip Kotler's marketing communication mix framework which encompasses advertising, sales promotion, events, public relations, online marketing, mobile marketing, direct marketing, and personal selling this study examines how amil zakat institutions at the local level apply modern marketing approaches within a socio-religious context. This study aims to analyze the marketing communication strategies implemented by Lazismu Cileungsi in disseminating zakat, infaq, and shadaqah, and to evaluate the effectiveness of their implementation. The research method employed was qualitative, with data collected through in-depth interviews with Lazismu Cileungsi managers, observation of communication activities on social media and in the field, and documentation review. The results indicate that Lazismu Cileungsi effectively utilizes digital media and personal approaches to reach the public, with public relations, online marketing, and direct marketing emerging as the dominant strategies. Although implementation has not been fully optimized in terms of sales promotion and large-scale events, a humanist and trust-based approach has been demonstrated to increase ZIS participation. These findings offer a practical contribution to managers of other Lembaga Amil Zakat (LAZ) at the local level, while enriching the academic study of nonprofit marketing communication in Indonesia.